Creating Radical Technologies and Competencies: Revisiting Interorganizational Dynamics in the Nascent Bionic Prosthetic Industry - Kim, Seojin; Agarwal, Rajshree; Goldfarb, Brent (Organization Science, 2026)
Why were incumbents able to pioneer and dominate the nascent bionic prosthetic industry, even though entrants represented the majority of the firms investing in this radical technology? To answer this question, our abductive study builds on the novel base principles definition and uses a historical approach to investigate the incubation and early commercialization periods (1974–2018) of bionic prosthetics. We use comprehensive quantitative data on all technological entrants and historical analysis of significant firms to reveal that organizational prehistory affects both the knowledge and intent of technological entrants. Start-ups, incumbents in conventional prosthetics, and established firms in other industries created and integrated subtechnologies into a radical system. Although all firms invested in component technologies, incumbents played a key role as system integrators. Incumbents dominated product commercialization; start-ups captured value through alliances or by being acquired, and established firms in other industries leveraged their knowledge in adjacent value chains as a function of their prior histories and intents. In comparing the virtues of our explanation—the creating radical systems effects—with widely accepted alternative explanations, we develop a more generalized framework of interorganizational dynamics in nascent industries as an endogenous, coevolutionary process that goes beyond explanations that privilege competitive dynamics to also include collaborative dynamics in value creation (and capture). Funding: This paper was funded by the Ed Snider Center for Enterprise and Markets at the University of Maryland, the Ewing Marion Kauffman Foundation and the Strategic Research Foundation. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.16915 .